2006
DOI: 10.1177/0146167205281009
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Stereotype Threat by Blurring Intergroup Boundaries

Abstract: Publisher's copyright statement:The nal denitive version of this article has been published in the Personality and social psychology bulletin, 32/4, 2006 c by the Society for Personality and Social Psychology, Inc. at the Personality and Social Psychology Bulletin page: http://journals.sagepub.com/doi/10.1177/0146167205281009Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 51 publications
3
90
1
1
Order By: Relevance
“…Stereotype threat is inherent in certain situations associated with negative stereotypes (Rosenthal & Crisp, 2006). Repeated exposure to images of Blacks as aggressive and intellectually inferior causes these images to be internalized, or, implicitly accepted as true of the group, and tragically, also perhaps of one's self (Fanon, 1952;Steele, 2011).…”
Section: Stereotype Threatmentioning
confidence: 99%
“…Stereotype threat is inherent in certain situations associated with negative stereotypes (Rosenthal & Crisp, 2006). Repeated exposure to images of Blacks as aggressive and intellectually inferior causes these images to be internalized, or, implicitly accepted as true of the group, and tragically, also perhaps of one's self (Fanon, 1952;Steele, 2011).…”
Section: Stereotype Threatmentioning
confidence: 99%
“…Evidence for the detrimental effects of stereotypes is now well established within social psychological research, with stereotype threat (US university students: Steele & Aronson, 1995) suggesting that individuals may underperform on tasks where their group is negatively stereotyped, due to fear of confirming the stereotype (US university students: Spencer, Steele, & Quinn, 1999). A proportion of the stereotype threat literature focuses on gender stereotypes with women underperforming on math tests (US university students: Brown & Josephs, 1999; UK university students: Rosenthal & Crisp, 2006), and engineering exams (Canadian university students : Bell, Spencer, Iserman, & Logel, 2003); while men underperform on social sensitivity (US university students: Koenig & Eagly, 2005) and affective tasks (French university students: Leyens, Désert, Croizet, & Darcis, 2000). Situations that induce underperformance for the negatively stereotyped group have also resulted in an improvement in performance for the comparison group.…”
mentioning
confidence: 99%
“…Rosenthal and Crisp 16 reported that having women focus on overlapping characteristics between sexes (a blurring intergroup bias intervention) before completing a test allowed them to answer more math questions correctly. Cohen and colleauges 17 demonstrated that a brief in-class writing "self-affirmation" assignment reinforcing individual self-worth through reflecting on positive group memberships improved the grades of African American students and reduced the racial achievement gap by 40%.…”
Section: Discussionmentioning
confidence: 99%